The power of visual storytelling : how to use visuals, videos, and social media to market your brand - Walter, Ekaterina; Gioglio, Jessica (New York : McGraw-Hill, 2014)
Filled with full-color images and thought-provoking examples from leading companies. The Power of Visual Storytelling explains how to grow your business and strengthen your brand by leveraging photos, videos, infographics, presentations, and other rich media. The book delivers a powerful road map for getting started, while inspiring new levels of creativity within organizations of all types and sizes.--[book cover]
Foreword / by Dan Roam -- Introduction -- The rise of visual storytelling -- Types, tips, and tactics of visual marketing -- The power of the platform : visual storytelling on social networks -- Developing a visual storytelling roadmap : from strategy to implementation -- Real-time marketing in a visual world.
Includes bibliographical references (pages 201-211) and index.
Keywords: Viral marketing; Internet marketing